2016
DOI: 10.1186/s12906-016-1354-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of 3-O-methyl quercetin and kaempferol from Semecarpus anacardium against H2O2 induced cytotoxicity in lung and liver cells

Abstract: BackgroundHydrogen peroxide is continuously generated in living cells through metabolic pathways and serves as a source of reactive oxygen species. Beyond the threshold level, it damages cells and causes several human disorders, including cancer.MethodsEffect of isolated 3-O-methyl quercetin and kaempferol on H2O2 induced cytotoxicity, ROS formation, plasma membrane damage, loss of mitochondrial membrane potential, DNA damage was evaluated in normal liver and lung cells. The RT-PCR analysis used to determine N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 42 publications
7
37
0
1
Order By: Relevance
“…The PCV, Hb concentration and total erythrocyte count were decreased. The findings from this study are in agreement with the results obtained by Kumar et al [49] and Minka and Ayo [50] who reported. That the decrease observed in the PCV, Hb and total erythrocyte count in the stressed rats may be due to increased lipid peroxidation in erythrocyte cell membranes and subsequent haemoglobin oxidation [50].…”
Section: Effect Of Zinc and Kaempferol On Haematological Indices Of Wsupporting
confidence: 94%
“…The PCV, Hb concentration and total erythrocyte count were decreased. The findings from this study are in agreement with the results obtained by Kumar et al [49] and Minka and Ayo [50] who reported. That the decrease observed in the PCV, Hb and total erythrocyte count in the stressed rats may be due to increased lipid peroxidation in erythrocyte cell membranes and subsequent haemoglobin oxidation [50].…”
Section: Effect Of Zinc and Kaempferol On Haematological Indices Of Wsupporting
confidence: 94%
“…KAE has been reported to upregulate Nrf2-mediated HO-1 expression (Hong et al, 2009) Kim, Ha, et al, 2008;Kumar, Bevara, Kaja, Badana, & Malla, 2016;Martin et al, 2004;Samhan-Arias, MartıƄ-Romero, & GutiĂ©rrez-Merino, 2004). These effects may also have been important for the significant reduction in ROS levels induced by KAE in the aged oocyte group in this study.…”
Section: Discussionmentioning
confidence: 51%
“…SOD, Nrf2 expression abnormalities and mitogen‐activated protein kinase (MAPK), phosphatidylinositol 3‐kinase (PI3K) signaling pathway disorder are key pathways for generating oxidative stress/damage (Ryter et al, ; Singh, Vrishni, Singh, Rahman, & Kakkar, ). KAE has been reported to upregulate Nrf2‐mediated HO‐1 expression (Hong et al, ), and relieve H 2 O 2 ‐induced oxidative stress by increasing the levels of p‐p38, Nrf2, SOD, and catalase (Kim, Lee, et al, ; Kim, Ha, et al, ; Kumar, Bevara, Kaja, Badana, & Malla, ; Martin et al, ; Samhan‐Arias, Martı́n‐Romero, & GutiĂ©rrez‐Merino, ). These effects may also have been important for the significant reduction in ROS levels induced by KAE in the aged oocyte group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It have been reported by scientific study recently to posse various properties like hypoglycemic, antiatherogenic, antimicrobial, antioxidant, anticarcinogenic, antiinflammatory, anti-reproductive, CNS stimulant, skin diseases and hair growth promoter [28][29][30][31][32][33]. It shows in vitro antioxidant properties and induces cytotoxicity in liver, lung [34,35], breast, leukaemia, cervical cancer cells [36,37] through induction of apoptosis [37,38]. It also has antitumor activity in tumor bearing rat [39,40] and mice model [41].…”
Section: Introductionmentioning
confidence: 99%